Effectiveness of Acupressure on the Taichong Acupoint in Lowering Blood Pressure in Patients with Hypertension: A Randomized Clinical Trial. (10th October 2016) - Lin, Gan-Hon; Chang, Wei-Chun; Chen, Kuan-Ju; Tsai, Chen-Chen; Hu, Sung-Yuan; Chen, Li-Li
Abstract : Objectives . To evaluate the effectiveness of acupressure on the Taichong acupoint in lowering systolic and diastolic blood pressure (BP) in hypertensive patients. Methods . Eighty patients with hypertension attending a cardiology outpatient department in central Taiwan were included in this randomized clinical trial. Acupressure was applied to the Taichong acupoint in the experimental group (n = 40 ) and to the first metatarsal (sham acupoint) in the control group (n = 40 ). Blood pressure was measured by electronic monitoring before and immediately 15 min and 30 min after acupressure. Results . The average age of the experimental and control participants was 59.3 ± 9.2 years and 62.7 ± 8.4 years, respectively. The two groups were similar for demographics and antihypertensive drug use. Mean systolic and diastolic BP in the experimental group decreased at 0, 15, and 30 min after acupressure (165.0/96.3, 150.4/92.7, 145.7/90.8, and 142.9/88.6 mmHg); no significant changes occurred in the control group. There was a significant difference in systolic and diastolic BP between the experimental and control groups immediately and 15 and 30 min after acupressure (p < 0.05 ). Conclusion . Acupressure on the Taichong acupoint can lower BP in hypertensive patients and may be included in the nursing care plan for hypertension. However, additional studies are needed to determine the optimal dosage, frequency, and long-term effects of this therapy.